HBHA-ECSIT interaction disrupts macrophage autophagy to promote Mycobacterium tuberculosis persistence - Li, Yongqiang; Jia, Xiuping; Wang, Xiaoying; Qiao, Huilian; Ma, Yueyun (Frontiers in Immunology, 2025)
Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb), remains one of the most significant global health challenges exacerbated by latent tuberculosis infection (LTBI). Heparin-binding hemagglutinin (HBHA), a virulence factor of Mtb, plays a critical role in LTBI by inhibiting autophagy in macrophages, though the underlying molecular mechanism has remained unclear. In this study, we identified the evolutionarily conserved signaling intermediate in Toll pathways (ECSIT) as a direct target of HBHA. Our experiments demonstrated that HBHA binds to ECSIT, disrupting the ECSIT-TRAF6 complex and inhibiting ECSIT ubiquitination in BCG-infected macrophages. Through genetic ablation studies in RAW264.7 macrophages, we found that ECSIT is indispensable for HBHA-mediated autophagy suppression, as evidenced by unchanged LC3-II conversion and Beclin-1 expression in ECSIT-knockdown RAW264.7 following HBHA treatment. Additionally, HBHA significantly enhanced intracellular mycobacterial survival in wild-type but not ECSIT-deficient macrophages, establishing ECSIT as an essential molecular nexus for HBHA-mediated bacterial persistence. Our findings reveal a novel mechanism by which Mtb exploits host ECSIT through HBHA to evade autophagic clearance, thereby promoting bacterial persistence. This study identifies the HBHA-ECSIT axis as a potential therapeutic target for host-directed interventions against tuberculosis.